Answer:
9.12 + 9.12 = 18.24 inches
Step-by-step explanation:
Diameter = 23 inches (given)
Radius = 11.5 inches
2 Chords of length = 14 inches ( You didn't specify if the 14 inches is for both chords or for a single cord. I'll assume it's for two cords 14 and 14inches apart.
To clearly solve this, we'll make some mild assumptions.
Let the perpendicular distance of the chords from the center of the circle to represented as " x and y"
Therefore:
x^2 + 7^2 = 11.5 ^ 2
x^2 + 49 = 132.25
x^2 = 132.25 - 49
x^2 = 83.25
x = √ 83.25
x = 9.12 inches
Since the cords have thesame length (Assumed from the way the question was structured, the distance would still be thesame)
y^2 + 7^2 = 11.5 ^ 2
y^2 + 49 = 132.25
y^2 = 132.25 - 49
y^2 = 83.25
y = √ 83.25
y = 9.12 inches
Therefore, the distance will be :
9.12 + 9.12 = 18.24 inches
Have fun!
To find the distance from each chord to the center of the circle, use the Pythagorean theorem to calculate the height of the isosceles triangle formed by the chord and two radii.
To find the distance from each chord to the center of the circle, we first need to find the radius of the circle. Since the diameter is given as 23 inches, the radius would be half of that, which is 11.5 inches. Now, let's consider one of the chords. When a chord is drawn in a circle, it forms an isosceles triangle with the center and two radii. The distance from the chord to the center of the circle is the height of this isosceles triangle. Using the Pythagorean theorem, we can find the height:
d² = r² - (c/2)²
where d is the distance from the chord to the center, r is the radius, and c is the length of the chord.
Plugging in the values, we get:
d² = (11.5)² - (14/2)²
Simplifying this equation gives:
d² = 132.25 - 49
d² = 83.25
Taking the square root of both sides gives:
d ≈ √83.25 ≈ 9.12 inches
#SPJ12
Answer:
4x = 4x+8
4x-4x=8
0=8
the equation is wrong
∅
Step-by-step explanation:
c. 171.755 years
d. 168.354 years
Answer:
A. 170.202
Step-by-step explanation:
Just took the test
Answer:a
Step-by-step explanation:test
3(5x + 10)
5(3x + 2)
Answer:
The expression 15x + 10 is equivalent to 5(3x+2)
Step-by-step explanation:
Hello, I think I can help you with this
factorize a polynomial is to break it down into two or more polynomials called factors, so that, by multiplying them, you get the original polynomial
step one
The expression 15x + 10 must be factorized, the common term between 15 and 10 is 5,
so , the answer is 5(3x+2)
Do not hesitate to ask me any questions you have,Have a fantastic day
Answer:
5(3X+2)
Step-by-step explanation:
16% -------- 58
100% ........ x
Cross multiply
100*58 = 16x
5800 = 16x
x= 5800/16
x = 363
I hope that's help !
answer with explanation
Answer:
18
Step-by-step explanation:
don't step answer. Because I am lol